Residual rock deformation of lined caverns for underground energy storage after air deflation considering stress path - Chen Xu; Caichu Xia; Gecheng Zhang; Sheng Wang; Hui Lu; Yingjun Xu (Journal of Rock Mechanics and Geotechnical Engineering)
This study investigates the mechanical response of an underground cavern subjected to cyclic high gas pressure, aiming to establish a theoretical foundation for the design of lined rock caverns (LRCs) for energy storage with high internal pressure, e.g. compressed air energy storage (CAES) underground caverns or hydrogen storage caverns. Initially, the stress paths of the surrounding rock during the excavation, pressurization, and depressurization processes are delineated. Analytical expressions for the stress and deformation of the surrounding rock are derived based on the Mohr–Coulomb criterion. These expressions are then employed to evaluate the displacement of cavern walls under varying qualities of surrounding rock, the contact pressure between the steel lining and the surrounding rock subject to different gas storage pressures, the load-bearing ratio of the surrounding rock, and the impact of lining thickness on the critical gas pressure. Furthermore, the deformation paths of the surrounding rock are evaluated, along with the effects of tunnel depth and diameter on residual deformation of the surrounding rock, and the critical minimum gas pressure at which the surrounding rock and the lining do not detach. The results indicate that residual deformation of the surrounding rock occurs after depressurization under higher internal pressure for higher-quality rock masses, leading to detachment between the surrounding rock and the steel lining. The findings indicate that thicker linings correspond to higher critical minimum gas pressures. However, for lower-quality surrounding rock, thicker linings correspond to lower critical minimum gas pressures. These findings will provide invaluable insights for the design of LRCs for underground energy storage caverns.